Task-Based Language Teaching (TBLT) in TESOL: Benefits and Challenges - Dilorom Poyonova; Sevara Abdishukurova; Makhliyo Shomurodova (Scientific Trends, 2025)
Task-Based Language Teaching (TBLT) is an innovative approach to TESOL that emphasizes the use of real-world tasks to promote language learning. This article examines the core principles of TBLT, its advantages in TESOL classrooms, the challenges it poses to both students and teachers, and practical strategies for effective implementation. The article also explores the impact of TBLT on student engagement and language proficiency.